Authenticity and the relevance of discourse and figured worlds in secondary students' discussions of socioscientific issues. (July 2017) - Åkerblom, Daniel; Lindahl, Mats
Abstract: The purpose of this paper is to examine how authenticity influences students' discussions of socioscientific issues (SSI). The students were found to bridge school knowledge and everyday knowledge, i.e. enter a "third space", in their explorative discussions. When the SSI task changed into a decision-making discussion for communication with an authentic stakeholder, the students excluded many perspectives. In the process, authenticity caused a loss of relevance for one discourse and several figured worlds, including the students' emotional reasoning. While losing emotional aspects, students' reasoning became more precise when grounded in rational reasoning, supporting well-informed decisions. Highlights: Authenticity can bridge the gap between students' everyday- and school knowledge. Authenticity determines the relevance of figured worlds in students' discussions. Interacting with authentic stakeholders improves students' rational reasoning.